Hegel e a ação política: considerações a partir da seção Moralidade da Filosofia do Direito - Madureira, Miriam Mesquita Sampaio (Revista Eletrônica Estudos Hegelianos, 2018)
In this paper I discuss the possibility of thinking political agency from Hegel´s theory of agency as exposed in the section Morality of the Philosophy of Right. After indicating to what extend a conception of political agency with the distance to ethical life which might be necessary for critique is not present in the Philosophy of Right itself (I.), I expose the conception of action developed in the section Morality of the Philosophy of Right (II) in order to discuss the legitimacy of applying this conception to the question of critique and political agency, in a sense compatible with the Hegelian notion of ethical life (III.). I conclude with some general reflexions on the possibilities of actualizing the resulting conception of political agency and its possible consequences for some contemporary debates (IV).